1997
DOI: 10.2754/avb199766010015
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Simplified Antipyrine Test in Calves

Abstract: The purpose of this study was to test a modification of antipyrine test in calves. The experiment was carried out on 10 calves (bulls of black and white breed). Each subject received on days 10 and 20 of life. respectively. 15 mg.kg· l body mass of antipyrine as an intravenous bolus injection. followed by its oral administration "in substantia" in gelatin capsules 48 hours later. The concentrations of antipyrine in their saliva were repeatedly determined. Pharmacokinetics of antipyrine was followed in each sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
1997
1997

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…The renal clearance of unchanged antipyrine slightly decreased after starvation for four days. The results from previous experiments reported by the authors (J anus et al 1997) indicated that renal excretion and clearance of unchanged antipyrine in calves was practically independent of diuresis and (generally) renal function.…”
Section: Discussionmentioning
confidence: 67%
“…The renal clearance of unchanged antipyrine slightly decreased after starvation for four days. The results from previous experiments reported by the authors (J anus et al 1997) indicated that renal excretion and clearance of unchanged antipyrine in calves was practically independent of diuresis and (generally) renal function.…”
Section: Discussionmentioning
confidence: 67%